Determination of Main Compositions in Phyllanthus Urinaria and its Effects on Cyp450 in Rats - Zhang, Zhennan; Sun, Zhe; Ye, Yaozhen; Wang, Xianqin (Current Pharmaceutical Analysis, 2020)
Background: Phyllanthus urinaria, a traditional herbal medicine, has aroused widespread concern at home and abroad. However, there are few studies on the effects of Phyllanthus urinaria on CYP450. Therefore, this study aims to explore the main chemical compositions of Phyllanthus urinaria and its effect on the activity of CYP450 enzyme in rats. Methods: Acetonitrile and 0.1% Trifluoroacetic Acid (TFA) were used as mobile phase, along with the application of gradient elution to simultaneously determine the main chemical constituents in Phyllanthus urinaria by HPLC (r2>0.999). Sprague-Dawley (SD) rats, randomly divided into control group, low-dose group and high-dose group, were treated with normal saline and different doses of Phyllanthus urinaria extract solution, respectively. Additionally, the rats were given intragastric administration of cocktail probe (specific substrates of CYP450 isoenzyme) at 15th day; the plasma was collected by tail vein at various times. Furthermore, the UPLC-MS/MS method (r2>0.99) was used to detect the probe concentration, along with the evaluation of the activity of CYP450 enzyme according to the pharmacokinetic parameters of the probe. Results: Gallic acid, 3, 4-dihydroxybenzoic acid, caffeic acid, corilagin and ellagic acid were found in the Phyllanthus urinaria extract solution by HPLC. Compared with the control group, the metabolism of bupropion, metoprolol, midazolam and tolbutamide slowed down significantly in the Phyllanthus urinaria group, with no significant metabolic changes in phenacetin. Conclusion: Phyllanthus urinaria could induce activity of CYP2D6, CYP2B1, CYP3A4 and CYP2C9, without exerting a significant effect on CYP1A2.
Keywords: HPLC